Flowering and trichome development share hormonal and transcription factor regulation - Matías-Hernández, Luis (Journal of experimental botany, 2016)
© The Author 2015. Published by Oxford University Press on behalf of the Society for Experimental Biology. All rights reserved. For permissions, please email: journals.permissionsoup.com.